2010 Fourth International Conference on Digital Society 2010
DOI: 10.1109/icds.2010.14
|View full text |Cite
|
Sign up to set email alerts
|

The All-In Publication Policy

Abstract: The productivity of scientists and the quality of their papers differ enormously. Still, all papers written get published eventually and the impact factor of the publication channel is not correlated to the citations that individual papers receive. Hence it does not matter where to publish papers. Based on these two conjectures, I conclude that all papers should be published. The review process should focus on feedback that helps authors to improve their manuscripts. But we should no longer waste effort to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It can therefore be argued that the filtering function of the peer review process is barely working. Instead it would be better to focus the review process on helping authors to improve their paper following the "All-In Publication Policy" (Bartneck 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It can therefore be argued that the filtering function of the peer review process is barely working. Instead it would be better to focus the review process on helping authors to improve their paper following the "All-In Publication Policy" (Bartneck 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Only very few are able to maintain a consistently high publication records over longer periods of time (Ioannidis et al, 2014). In part this could be due to the lack of the papers' quality, but it has also been pointed out that the review process in itself is faulty and that (almost) every paper that is written gets published eventually Bartneck (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Carayol and Mireille (2004) showed that such passive researchers significantly decrease the productivity of research labs. This competition has reached a level at which considerable negative side effects start to emerge (Bartneck, 2010). Not only do the members of academia suffer from enormous stress (Herbert et al, 2014), job insecurity and lack of career perspectives, the funding system as it operates right now might not be the most efficient.…”
Section: Introductionmentioning
confidence: 99%